2018
DOI: 10.1016/j.neuint.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between mitochondrial function, iron, copper and glutathione in Parkinson's disease

Abstract: Parkinson's disease is neuropathologically characterised by loss of catecholamine neurons in vulnerable brain regions including substantia nigra pars compacta and locus coeruleus. This review discusses how the susceptibility of these regions is defined by their shared biochemical characteristics that differentiate them from other neurons. Parkinson's disease is biochemically characterised by mitochondrial dysfunction, accumulation of iron, diminished copper content and depleted glutathione levels in these regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 191 publications
(244 reference statements)
3
31
0
Order By: Relevance
“…A more stable pool of metals may be represented by plasma bound organelles such as mitochondria, which internalise Fe, Cu, Mn and Zn for both specific biological function or the synthesis of metalloproteins such as Fe-sulfur complexes or cytochrome c oxidase. Although mitochondrial dysfunction, and resulting effects on metal levels, are proposed to contribute to neuronal death in Parkinson’s disease, 32 the fractionation technique used here may have masked subtle changes in mitochondrial metal levels and specific isolation of mitochondria from other membrane-encapsulated metals in Parkinson’s disease and control samples would be required.…”
Section: Discussionmentioning
confidence: 99%
“…A more stable pool of metals may be represented by plasma bound organelles such as mitochondria, which internalise Fe, Cu, Mn and Zn for both specific biological function or the synthesis of metalloproteins such as Fe-sulfur complexes or cytochrome c oxidase. Although mitochondrial dysfunction, and resulting effects on metal levels, are proposed to contribute to neuronal death in Parkinson’s disease, 32 the fractionation technique used here may have masked subtle changes in mitochondrial metal levels and specific isolation of mitochondria from other membrane-encapsulated metals in Parkinson’s disease and control samples would be required.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropathological features of PD are the loss of catecholamine neurons in vulnerable brain regions, including substantia nigra (SN) pars compacta (SNc) and blue spot, and the PD is biochemically characterized by mitochondrial dysfunction, accumulation of iron, diminished copper content, and depleted GSH levels in these regions (Liddell and White, 2018). It was beneficial for PD when using ferroptosis inhibitor-iron chelator deferiprone for PD treatment in a randomized controlled trial (Devos et al, 2014), and deferiprone could protect SN neurons and prevent PD progression in this trial.…”
Section: Ferroptosis In Parkinson's Diseasementioning
confidence: 99%
“…So it is concluded that ferroptosis may play an important role in the progression of PD disease, and that PD has been undergoing clinical evaluation through a conservative chelation mode based on drug-mediated iron redistribution (Moreau et al, 2018), and it might be a chance to cure PD in the future. Mitochondrial damage occurs in the early stages of PD and a large body of evidence indicates that the activity of mitochondrial complex | was impaired in tissues after the death of PD, and another typical feature of PD was that GSH is selectively depleted from the (Liddell and White, 2018). These characteristics are the most typical characteristics of ferroptosis, suggesting that ferroptosis may play a key role in the progression of PD disease.…”
Section: Ferroptosis In Parkinson's Diseasementioning
confidence: 99%
“…Copper's general role in redox and oxidative stress is pertinent to SCN clock function and neurodegeneration. A proportional balance of Cu and reduced glutathione/GSH are important for decreasing oxidative damage and increasing cell survival, particularly in response to neurotoxic conditions (Du et al., ; Hatori, Clasen, Hasan, Barry, & Lutsenko, ; Kumar, Kalita, Bora, & Misra, ; Liddell & White, ; Mercer et al., ; Samuele et al., ; White & Cappai, ; White et al., ). Mitochondrial energetics plays a critical role in determining cellular Cu distribution and metabolism along with ROS and GSH levels; highly metabolically active neurons must coordinate antioxidant processes to protect against ROS/oxidative stress (Grimm & Eckert, ; Requejo‐Aguilar & Bolanos, ; Stefanatos & Sanz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is evidence that Cu can modulate transcription in mammalian (Kamiya, Takeuchi, Fukudome, Hara, & Adachi, ; Yan et al., ) and nonmammalian cells (Park et al., ; Sameach et al., ), either directly or indirectly. For example, Cu can modulate phosphodiesterases and phosphatases, as well as several transcription factors (SP1, AP1, NRF2) (Chen et al., ; Jiang et al., ; Liddell & White, ; Mattie et al., ). Notably, some of these pathways and potential interacting, elements (e.g., JNK, GSK3, FoxO signaling) play a role in circadian rhythms, highlighting a need to investigate their interaction with Cu in the SCN (Asher & Schibler, ; Barthel, Ostrakhovitch, Walter, Kampkotter, & Klotz, ; Besing et al., ; Hamann, Petroll, Grimm, Hartwig, & Klotz, ; Kon, Sugiyama, Yoshitane, Kameshita, & Fukada, ; Mattie et al., ; Paul et al., ; Sun et al., ; Wu et al., ; Yoshitane et al., ; Zheng et al., ).…”
Section: Introductionmentioning
confidence: 99%